Influence of tin (IV) doping on structural and optical properties of rhombohedral barium titanate (BaTiO3). (2021) - Selvaraj, M.; Venkatesan, R.; Mayandi, J.; Venkatachalapathy, V.
Abstract: The impact of tin (IV-Sn 4+ ) doping into rhombohedral barium titanate (BaTiO3 ) towards the enhancement of second harmonic generation (SHG) was studied. XRD analysis confirms retention of rhombohedral symmetry in Sn 4+ doped BaTiO3 . UV-Vis absorption study reveals that Sn 4+ doping has no significant effect on the optical band gap of BaTiO3 . Raman spectrum portrays that undoped and Sn 4+ doped BaTiO3 nanopowder exhibits Raman active modes of rhombohedral symmetry. The studies displays that Sn 4+ doped BaTiO3 has created non-centrosymmetry, which could be utilized for enhancement in SHG and possibility to improve the efficiency in rhombohedral BaTiO3 based solar cells.